Clinicopathological association of CD44 and PD-L1 expression in epithelial ovarian carcinoma: a hospital-based cross-sectional study from AIIMS Patna - Saroj, Manish Kumar; Bhadani, Punam Prasad; Kumar, Tarun; Nigam, Jitendra Singh; Anant, Monika (International Journal of Research in Medical Sciences, 2025)
Background: Epithelial ovarian carcinoma (EOC) is the most lethal gynecological malignancy, often presenting at advanced stages. Molecular markers such as CD44, a stem cell-associated adhesion molecule, and PD-L1, an immune checkpoint regulator, have been implicated in tumor progression, chemoresistance, and immune evasion. Understanding their expression patterns and correlation with clinicopathological features may aid prognostic stratification and therapeutic decision-making. Aim was to assess CD44 and PD-L1 expression in EOC and analyze their association with clinicopathological parameters. Methods: A hospital-based cross-sectional study was conducted over 5 years (2018-2023) in the department of pathology, AIIMS Patna. A total of 132 histologically confirmed cases of EOC were included. Immunohistochemistry (IHC) for CD44 and PD-L1 was performed, and expression was scored semi-quantitatively. Associations with age, histological subtype, tumor grade, stage, and lymph node involvement were evaluated. Statistical analysis was performed using chi-square and logistic regression. Results: CD44 positivity was observed in 79/132 cases (59.8%), while PD-L1 was expressed in 62/132 cases (47.0%). Co-expression of both markers was found in 38 cases (28.8%). High CD44 expression was significantly associated with high-grade serous carcinoma (p=0.01), advanced FIGO stage (p=0.03), and lymph node metastasis (p=0.04). PD-L1 positivity correlated with advanced stage (p=0.02) and presence of ascites (p=0.03). Co-expression was linked to poor differentiation and advanced disease. Multivariate analysis showed CD44+/PD-L1+ tumors had 2.6-fold higher odds of lymph node metastasis. Conclusions: CD44 and PD-L1 are frequently expressed in EOC and show significant association with adverse pathological features. Their combined expression may serve as a prognostic biomarker and highlight potential candidates for targeted and immune checkpoint therapies in ovarian carcinoma.